2016
DOI: 10.1007/s00134-016-4258-y
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of cardiac output measurements by echocardiography vs. thermodilution: the techniques are not interchangeable

Abstract: The majority of studies comparing echocardiography with thermodilution were difficult to interpret, but current evidence does not support interchangeability between these techniques in measuring cardiac output. The techniques may be interchangeable in tracking directional changes in cardiac output, but this has to be confirmed in large high-quality studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 64 publications
3
62
0
1
Order By: Relevance
“…Either transthoracic or transoesophageal echocardiography may be used to estimate cardiac output. However, few studies have validated the accuracy of echocardiography compared to the ‘gold standard’ pulmonary artery catheter (PAC) . One recent study in 38 mechanically ventilated patients found high correlation (r=0.95) between cardiac output measured by PAC and cardiac output measured by transthoracic echocardiography .…”
Section: Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Either transthoracic or transoesophageal echocardiography may be used to estimate cardiac output. However, few studies have validated the accuracy of echocardiography compared to the ‘gold standard’ pulmonary artery catheter (PAC) . One recent study in 38 mechanically ventilated patients found high correlation (r=0.95) between cardiac output measured by PAC and cardiac output measured by transthoracic echocardiography .…”
Section: Imagingmentioning
confidence: 99%
“…One recent study in 38 mechanically ventilated patients found high correlation (r=0.95) between cardiac output measured by PAC and cardiac output measured by transthoracic echocardiography . The techniques are not interchangeable when measuring cardiac output, but they may be interchangeable to follow directional changes in cardiac output …”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the critical care setting, few studies have evaluated the level of concordance between CO estimated by TTE (CO-TTE) and CO estimated by PAC (CO-PAC) [4–6]. In these studies, Bland–Altman analyses have evidenced a small level of bias and a broad limit of agreement (LOA).…”
Section: Introductionmentioning
confidence: 99%
“…However, other methods have not been properly validated for monitoring, e.g. cardiac output measurements by echocardiography [14]. Taken together, there is no high-quality evidence indicating improved patient care and outcomes with the use of any haemodynamic tool in critically ill patients.…”
Section: Why Are the Advanced Haemodynamic Tools Not Used To Guide Flmentioning
confidence: 99%